A Structural Vector Autoregression Model for Monetary Policy Analysis in India. (November 2014) - Paramanik, Rajendra Narayan; Kamaiah, Bandi
A structural vector autoregression (SVAR) model is proposed for analysing the impact of monetary policy stances on real variables in the Indian economy, in the context of its continuous exposure to global factors like oil price shocks and changes in global financial health. The empirical findings based on monthly data relating to the post-liberalisation period (April 1992–December 2012) suggest that contractionary monetary policy has had a considerable adverse impact on output for a year, which appears to be consistent with the prevailing economic outlook. But the same policy measure fuels inflation further for the first eight months in contrast to its expected decline, and the rise in inflation raises the issue of a 'price puzzle' in the Indian context. Monetary policy-induced exchange rate appreciation hampers industrial production due to outperformance of high import demand over export competitiveness and causes an increase in the average price level. Global factors like oil price shocks leave detrimental effects on output for a long time horizon of 10–12 months and raise inflation for nearly half a year, whereas an increase in the US federal funds rate results in a temporary decline in output growth of Indian industries. JEL Classification: C01, E43, E52